Kant’s highest Good: The Moral Law’s constructed Object - Villarán, Alonso (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This article has three goals: a. to compile the criticisms presented against Kant’s highest good (a world in which virtue is rewarded with happiness); b. to elaborate a critical review of the corresponding defenses; and c. to develop a new defense, with emphasis in the problem of derivation (according to which the highest good cannot be derived from the moral law). Regarding the first point, the article shows that that there at least are five problems that threaten the doctrine: heteronomy, derivation, impossibility, irrelevance, and dualism. Regarding the second, the article reveals that the multiple defenses developed in the name of the highest good are source, in turn, of other problems, such as those of incompleteness, illusion, injustice, disloyalty, and splitting. Regarding the third and main point, and starting with the derivation, the article proposes to see the highest good as the constructed object of the moral law. Once with the problem of derivation solved, the article offers short answers to the other problems involved. The article also translates for the first time, from English to Spanish, fragments of important publications regarding the highest good.
Keywords: Kant; ethics; moral law; virtue; happiness; highest good.